The letters of M. Valančius to A. Zavadsky - Tyla, Antanas (Literatūra, 1969)
These letters (1852-62) of M. Valančius, Bishop of Žemaitija (Samogitia), to A. Zavadsky, the known printer and publisher in Vilnius, are presented. The letters mainly deal with the publishing and distribution of Lithuanian books and pamphlets. Here are given new data which will help to specify each separate edition of different books printed. At the same time it touches upon a lot of problems which are very important to an investigator of Lithuanian culture; such as the problem of opening a book-store in Varniai, efforts of establishing a printing-house at the place, relations between M. Valančius and S. Daukantas, general problems of enlightenment, etc.